#TITLE_ALTERNATIVE# - SETIASIH (NIM : 101 06 064) Dosen Pembimbing : Dr. Agus Yodi Gunawan, WIWIN
In this final project, we derive a mathematical model describing a geothermal eruption process in which fluid flow occurs vertically from under the earth to the surface of the earth. Model eruption is devided into two parts. Under and above the ground eruptions. Along the discussion, the process is assumed to be independent of time and depth-dependent only. Our analysis is restricted to the under the ground eruption. The resulting equation for the eruption process under the ground is made such that only depends on temperature, and made the calculations numerically so that generated some graphs relationship between pressure, temperature, depth, and velocity of the fl uid. Result show that the lower the temperature, the smaller the pressure is and the higher the fluid velocity is. Knowing the velocity of fluid when an eruption occurs, we may compute discharge of fluid flowing to the surface of the earth.